STRATEGY MODEL FOR DEVELOPMENT OF COMMUNITY-BASED ECOTOURISM MANAGEMENT IN JATILUWIH TOURISM VILLAGE, TABANAN REGENCY - Ketut Sudarmini; Ni Nengah Ganawati; Ni Ketut Sariani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Jatiluwih Village is a village located in Penebel sub-district, Tabanan regency, Bali province, Indonesia. Jatiluwih is a tourist village, with a beautiful panorama accompanied by stepped rice fields. The air is cool because it is located at an average height of 700 meters above sea level Jatiluwih Village located in Tabanan Regency, Bali has a unique natural scenery of the widest terraced rice fields and the charm of the waterfall, to become a world cultural heritage. Jtiluwih village is very famous for the stunning natural beauty of terraced rice fields. The beauty of this terraced rice field is also used as one of the best tourist destinations in Tabanan. In addition to the beauty of rice fields, there are many attractions owned by this Jatiluwih Bali Village tourist spot. Not far from the tourist attractions of Jatiluwih Village Bali, there is Yeh Hoo Waterfall hidden behind a moor. The path to get there is also not too difficult, just go down the stairs. In addition to the waterfall object, Jatiluwih Village also has the charm of the expanse of rice fields so wide, that it makes the eye satisfied to see directly the Balinese farmers who are farming rice. Most of the rice fields in this tourist village produce rice. In addition, there are also crops of vegetables, coffee, coconuts, and much more. Tourism village development requires the participation of local communities in all stages of development starting from the planning, implementation, and supervision stages. However, in reality there is often a neglect of community participation. Jatiluwih Village has extraordinary potential and is very important to be developed as an ecotourism village that can increase the income of the village and the surrounding community, for that this study specifically, aims to: (1) analyze the potential of ecotourism in Jatiluwih Village, Tabanan Regency; (2) analyze internal and external conditions in ecotourism development in Jatiluwih Village, Tabanan Regency; (3) formulate a model of ecotourism development strategy in Jatiluwih Tourism Village, Tabanan Regency. This study used a qualitative descriptive research approach. This research also uses an internal and external environment analysis approach followed by a SWOT analysis.